Maternal-Fetal Circadian Communication During Pregnancy - Bates, Keenan; Herzog, Erik D. (Frontiers in Endocrinology, 2020)
This article reviews evidence for maternal-fetal communication about the time of day. We explore the hypothesis that key maternal hormones synchronize daily rhythms in the fetus to regulate gestation duration. These findings may help to predict and prevent preterm birth.